Pertanggungjawaban Pidana Selebritas Instagram Yang Terlibat Dalam Promosi Judi Online. - Wayan Santoso; Anak Agung Gede Agung Indra Prathama; I Made Atha Rimbawa (Lembaga Penelitian Pengabdian Masyarakat dan Pusat Kajian - Universitas Ngurah Rai, 2026)
The development of information and communication technology has brought significant changes to patterns of social interaction within society, particularly through the use of social media. The promotion of online gambling by Instagram celebrities (selebgram) through social media raises issues of criminal liability under Indonesian law. Selebgrams play a role in disseminating prohibited gambling content, thereby potentially expanding online gambling practices. This study aims to analyze the criminal liability of selebgrams who promote online gambling under Indonesian criminal law. This research employs a normative legal method with a statutory approach. The findings indicate that selebgrams who intentionally promote online gambling may be held criminally liable under the Electronic Information and Transactions Law and relevant provisions of the Indonesian Criminal Code.